Sonochemical Synthesis and Characterization of Copper Oxide Nanoparticles - Narongdet Wongpisutpaisan; Piyanut Charoonsuk; Naratip Vittayakorn; Wisanu Pecharapa (My University, 2011)
Copper oxide (CuO) nanoparticles were synthesized by a sonochemical process using copper nitrate and sodium hydroxide in the presence of polyvinyl alcohol (PVA) as a starting precursor. The precipitated product was calcined at various temperature ranging from 400-700 °C.The physical microstructure and morphology of as-calcined nanoparticles were characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM). From XRD observation, it is evident that the high purity CuO nanoparticles were obtained by this synthesis process. It was additionally revealed that its crystallization and particle size was strongly dependent on the reaction time and calcination temperature.
Keywords: Polyvinyl Alcohol; Sodium hydroxide; Copper oxide; Copper-based nanomaterials and applications